DIGITAL TRANSFORMATION OF ONLINE LEARNING TOOLS ADOPTED BY HIGHER EDUCATION INSTITUTIONS IN HARYANA DURING THE PANDEMIC (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The COVID-19 pandemic has precipitated  unprecedented changes across various  sectors, with education being one of the most  significantly impacted. As higher education  institutions swiftly transitioned from traditional  in-person teaching methods to online platforms,  the need to assess and understand this digital  transformation has become critical. This  research paper explores the adoption of online  learning tools by higher education institutions  in Haryana during the pandemic, employing a  qualitative research methodology to gain deeper  insights into the experiences, challenges, and  outcomes associated with this shift.
Keywords: Digital Transformation Learning Tools in Higher Education Institutions (HEIs) in Haryana.